Studi Perbandingan dan Hubungan Antara Densitas dan Kuat Tekan Tanah Laterit pada Lapisan Limonit dan Saprolit di Area Penambangan Nikel di Kecamatan Lasolo - Rizki Kumalasari; La Ode Dzakir; Hariono Hariono; Muhamad Karnoha Amir (Jurnal Geomine, 2023)
Differences in the degree of weathering in the lateritic soil zoning will cause differences in the strength or compressive strength of the lateritic soil material. To find out the difference in strength or compressive strength of soil material, it is necessary to test the physical properties and mechanical properties of the soil material. This research activity aims to obtain information regarding the values of density and compressive strength and to determine the relationship between density and compressive strength of soil material in limonite and saprolite soil layers. From this research activity, it is known that the density value of the soil material in the limonite layer is greater than that of the saprolite layer, while the compressive strength value of the soil material in the limonite layer shows a higher compressive strength value compared to the saprolite layer. In addition, the results of this study, it is also known the relationship between density and compressive strength of lateritic soil, namely the greater the density value of the lateritic soil material, the greater the compressive strength value, and vice versa, the smaller the rock density value, the smaller the compressive strength value.